Epidural Venous Plexus Engorgement: What Lies Beneath? - Fuldem Yildirim Donmez (Case Reports in Radiology)
Epidural venous plexus engorgement may occur due to several conditions that prevent the normal venous circulation. Inferior vena cava agenesis is a very rare cause of epidural venous enlargement. We present a case with a very thin inferior vena cava and left iliac vein agenesis who presented with back pain due to epidural vein engorgement and lacked other venous problems such as deep vein thrombosis.